Consensus control via iterative learning for distributed parameter models multi-agent systems with time-delay. Issue 10 (July 2019) - Dai, Xisheng; Wang, Cun; Tian, Senping; Huang, Qingnan
Abstract: Most of the available results of iterative learning control (ILC) are that solve the consensus problem of lumped parameter models multi-agent systems. This paper considers the consensus control problem of distributed parameter models multi-agent systems with time-delay. By using the knowledge between neighboring agents, considering time-delay problem in the multi-agent systems, a distributed P -type iterative learning control protocol is proposed. The consensus error between any two agents in the sense of L 2 norm can converge to zero after enough iterations based on proposed ILC law. And then we extend these conclusions to Lipschitz nonlinear case. Finally, the simulation result shows the effectiveness of the control method.